Heat stress exposure cause alterations in intestinal microbiota, transcriptome, and metabolome of broilers - Liu, Xuan; Ma, Zhenhua; Wang, Yanfei; Jia, Hao; Wang, Zheng; Zhang, Lihuan (Frontiers in Microbiology, 2023)
Heat stress can affect the production of poultry through complex interactions between genes, metabolites and microorganisms. At present, it is unclear how heat stress affects genetic, metabolic and microbial changes in poultry, as well as the complex interactions between them. Thus, at 28 days of age a total of 200 Arbor Acres broilers with similar body weights were randomly divided into the control (CON) and heat stress treatment (HS). There were 5 replicates in CON and HS, respectively, 20 per replication. From the 28-42 d, the HS was kept at 31 ± 1 ℃ (9:00-17:00, 8 h) and other time was maintained at 21 ± 1 ℃ as in the CON. At the 42nd day experiment, we calculated the growth performance (n = 8) of broilers and collected 3 and 6 cecal tissues for transcriptomic and metabolomic investigation and 4 cecal contents for metagenomic investigation of each treatment. The results indicate that heat stress significantly reduced the average daily gain and body weight of broilers (P-value < 0.05). Transcriptome KEGG enrichment showed that the differential genes were mainly enriched in the NF-kB signaling pathway. Metabolomics results showed that KEGG enrichment showed that the differential metabolites were mainly enriched in the mTOR signaling pathway. 16S rDNA amplicon sequencing results indicated that heat stress increased the relative abundance of Proteobacteria decreased the relative abundance of Firmicutes. Multi-omics analysis showed that the co-participating pathway of differential genes, metabolites and microorganisms KEGG enrichment was purine metabolism. Pearson correlation analysis found that ornithine was positively correlated with SULT1C3, GSTT1L and g_Lactobacillus, and negatively correlated with CALB1. PE was negatively correlated with CALB1 and CHAC1, and positively with g_Alistipes. In conclusion, heat stress can generate large amounts of reactive oxygen and increase the types of harmful bacteria, reduce intestinal nutrient absorption and antioxidant capacity, and thereby damage intestinal health and immune function, and reduce growth performance indicators. This biological process is manifested in the complex regulation, providing a foundational theoretical basis for solving the problem of heat stress.